Central Venous Access Capability and Critical Care Telemedicine Decreases Inter-Hospital Transfer Among Severe Sepsis Patients: A Mixed Methods Design - Ilko, Steven A. (Crit Care Med, 2019)
OBJECTIVE: Severe sepsis is a complex, resource intensive, and potentially lethal condition, and rural patients have worse outcomes than urban patients. Early identification and treatment are important to improving outcomes. The objective of this study was to identify hospital-specific factors associated with inter-hospital transfer. DESIGN: Mixed method study integrating data from a telephone survey and retrospective cohort study. PARTICIPANTS AND PATIENTS: Survey of Iowa Emergency Department (ED) administrators between May and June 2017 and cohort of adults seen in Iowa EDs for severe sepsis and septic shock between January 2005 and December 2013. INTERVENTIONS: None MEASUREMENTS AND MAIN RESULTS: Multivariable logistic regression was used to identify independent predictors of inter-hospital transfer. We included 114 institutions that provided data (response rate= 99%), and responses were linked to a total of 150,845 visits for severe sepsis/septic shock. In our adjusted model, having the capability to place CVCs or having a subscription to a CC-telemedicine service was independently associated with lower odds of inter-hospital transfer (aOR: 0.69, 95%CI: 0.54–0.86; aOR: 0.69, 95%CI: 0.54–0.88 respectively). A facility’s participation in a sepsis-specific quality improvement initiative was associated with 62% higher odds of transfer (aOR: 1.62, 95%CI: 1.10–2.39). CONCLUSIONS: The insertion of CVCs and access to a critical care physician during sepsis treatment are important capabilities in hospitals that transfer fewer sepsis patients. In the future, hospital-specific capabilities may be used to identify institutions as regional sepsis centers.